Samuel Sloan journal - Sloan, Samuel, active 1799-1806.
Journal (1799 July 13-1806 June 15) kept by Sloan while serving aboard the USF Constitution.
Seaman.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Navy -- History; Constitution (Frigate); Seamen